Optimizing Children's Knowlegdge Through Comic Media in Preventing Violence Againts Children - Mardiyah, Siti; Windyastuti, Erlina; Ardiani, Nurul Devi; Prastiwi, Firman; Owa, Maria Goreti (Universitas Malahayati Lampung, 2025)
ABSTRACT Child abuse refers to any act or treatment that has the potential to harm children, resulting in disability or even death. Educational health promotion plays an important role in reducing the negative impacts of child abuse by increasing awareness of prevention. One of the educational media used was comics, due to their attractive and easy-to-understand format. To increase knowledge and prevent violence against children. The community service activities were conducted in the Kadipiro RW 13 area and through a webinar involving participants from Timor Leste. The activity involved 20 mothers with children as participans. The results of the activity showed that the knowledge of participants was 85%. The conclusion of the implementation of this community service activity was that it increased the knowledge of mothers. This community service activity effectively increased the knowledge of mothers and served as one step in building an environment that supports the mental health of the Indonesian people. Keywords: Education, Violence Against Children, Comics